Time travel trouble - Seegert, Scott (Seegert, Scott. Vordak the Incomprehensible, 2013)
In an attempt to finally best his arch-nemesis, Commander Virtue, supervillain Vordak the Incomprehensible attempts traveling back in time, with disastrous results.